Physiotherapy Services: Core Stability Exercises are Essential for Reducing Lower Back Pain (LBP) in the Elderly - Ghufroni, Afif; Pertiwi, Jasmine; Wahyono, Yulianto (Poltekkes Kemenkes Surakarta, 2025)
Background: Low back pain (LBP) is a common health problem among the elderly, often interfering with daily activities and reducing quality of life. Aging affects the spine’s structure and function, increasing the risk of LBP. Non-pharmacological interventions such as core stability exercises have shown potential in reducing pain and improving function. This training program improved the knowledge and skills of both health cadres and older adults, making it a useful non-pharmacological therapy to enhance quality of life. Methods: This community service program was conducted in Tohudan Village, Karanganyar, Central Java, from February to July 2023, involving elderly individuals experiencing LBP and local health cadres. The intervention included educational sessions, training in core stability exercises, and evaluations of participants’ knowledge and skills. The exercises taught included diaphragmatic breathing, raising limbs, bridging, and quadruped positions. The evaluation was conducted through structured qualitative interviews with participants and cadres. Results: The program showed positive outcomes, with increased understanding and skill among health cadres and elderly participants in performing core stability exercises. Interviews with participants and cadres supported these findings—participants reported reduced pain and improved ability to perform daily activities after regular exercise, while cadres felt more confident in guiding others to perform correctly and maintaining programme continuity. Conclusion: Core stability exercise is an effective non-pharmacological intervention to reduce low back pain and improve the quality of life among the elderly. Training community health cadres ensures sustainable impact, enabling continued support for elderly individuals suffering from LBP. Further referrals to health facilities are recommended if symptoms persist.